The Apocryphal Bulgarian Sermon of Saint John Chrysostom on the Оrigin of Paulicians and Manichean Dimensions of Medieval Paulician Identity - Saldzhiev, Hristo (Studia Ceranea, 2020)
The article deals with one of the medieval Bulgarian sources about the origin of Paulicianism – the so called Sermon of Saint John Chrysostom on the Оrigin of Paulicians. On the basis of linguistic, textological and historical analysis it is concluded that the “sermon” appears to be a popular “contra version” of an unknown Paulician myth of historical and religious identity. It is suggested a reconstruction of this supposed myth and its obvious connections with Manicheism are traced out. Finally the traces of Manicheism in Paulician belief system are discussed.